Aspects of Humoral Immunity in a Group of Children With Type 1 Diabetes and Thyroid Disorders - Adriana, Gherbon (European Scientific Journal, ESJ, 2016)
Patients with diabetes have a high prevalence of thyroid disease compared with non-diabetic population. In the case of type 1 diabetes, it is often associated with autoimmune endocrine and systemic diseases as: Graves-Basedow disease, autoimmune chonic thyroiditis (ACT), Addison’s disease, celiac disease, pernicious anemia, myasthenia gravis, vitiligo, etc.. The purpose of this study is to determine the main aspects of humoral immunity in a group of children with type 1 diabetes and thyroid disorders. The studied group was represented by 83 cases (71 girls and 12 boys), aged between 7-17 years. They were used clinical, imaging, biochemical, hormonal and immunological parameters. Results: Prevalence of positive anthyroid antibodies (ACAT) in the study group was: Basedow â€“ Graves disease â€“ 100% (both), ACT - 85.18% antiTPO and 83.33% antiTg, euthyroid difusse goiter â€“ 0% (both). In the case of children and adolescents with type 1 diabetes and ACT with positive antiTPO AB we notice that they had a younger onset age of diabetes (4.86 Â± 3.94 vs. 8.62 Â± 0.51 years), a longer duration of diabetes (9.23 Â± 4.05 vs. 8.12 Â± 0.64 years), elevated HbA1c values (8.91 Â± 2.03 vs.7, 55 Â± 1.96%) and lower TSH values (12.00 Â± 23.7 vs. 14.77 Â± 17.03 mIU/ml) than those negative. Conclusions: It is recommended determination of antithyroid antibodies, particularly those antiTPO in children and adolescents with type 1 diabetes at onset of diabetes, or before puberty and, if they are positive should be tested the thyroid function annually to minimize the risk of undiagnosed hypothyroidism.